(untitled) (Contemporary Journal of Social Science Review, 2025)
This study examines how Orientalism has functioned not merely as an intellectual or scholarly tradition but as a key instrument in shaping global policy and political narratives. The Middle East and the Muslim world have frequently been represented through orientalist frameworks, producing interpretations that legitimized colonial and post-colonial policies. Such narratives often portrayed Muslim societies as politically stagnant, socially backward, and culturally dependent on the West, thereby influencing both public opinion and international strategies.The article analyzes how orientalist thought has framed major political and economic issues in the Middle East—such as democracy, secularism, terrorism, energy politics, and religious identity—and how these interpretations have guided global policymaking. Furthermore, it explores the internal political representations within the Muslim world, where local leadership and institutions have often drawn upon or been constrained by orientalist discourses in shaping their strategies.The study concludes that contemporary global politics continues to be significantly influenced by the orientalist legacy in defining policies toward the Muslim world. It also highlights the urgent need for Muslim societies to construct alternative intellectual and policy frameworks in order to articulate a more balanced, realistic, and autonomous narrative at the international level.